Bioconversion of lignocellulosic waste to bioethanol by Trichoderma and yeast fermentation - Saravanakumar, K. (Springer Berlin Heidelberg, 2013)
The present work aimed at producing bioethanol using lignocellulosic waste sawdust and marine yeast fermentation. Lignocellulosic waste materials were converted into monosugars through acid hydrolysis and finally treated with cellulase enzyme derived from Trichoderma/Hypocrea. To enhance the conversion of the glucose from sawdust, the experimental conditions were statistically optimized. The efficient conversion of sawdust to glucose of 78.56 % was achieved under the conditions of pH 6.19, temperature 29 °C, cellulase enzyme (8.16 IU ml(−1)) and sawdust (7.95 g l(−1)). The lignocellulosic waste-sawdust hydrolysis was used as the carbon source for the production of bioethanol. Bioethanol production of 85.6 % was achieved (55.2 g l(−1)) under the optimized conditions of temperature of 36.5 °C, incubation time of 102 h and enzyme-treated sawdust of 45.14 ml l(−1) and agitation of 330 rpm. This work achieved maximum bioethanol production using H.estonica and S.cerevisiae fermentation.